Expressão heteróloga e utilização da proteína recombinante EMA-1 de Theileria equi como imunobiológico - Nizoli, Leandro Quintana (2009)
Equine theileriosis is considered to be one of the most important parasitic diseases that affect horses, and has great economic impact on the equine industry. The disease is caused by the etiologic agent Theileria equi, which is classified as a hematozoan. The losses associated with equine theileriosis are related to clinical manifestation as well as restriction to international travel to positive horses. Chronic infected equines suffer the risk of the disease relapse which leads to losses in reproduction performance and are potentially disseminators of the disease. In the last years, studies on the immunologic diagnosis and vaccination against T. equi have focused to obtain distinct antigenic proteins. On the outer membrane of this protozoan, major surface proteins has been characterized and named as EMAs (equi merozoite antigen). Of these, EMA-1 has been used as antigen for diagnosis due to its conservation in diverse isolates. Its role as a potential immunogen has been well documented due its ability to stimulate a humoral response with production of specific antibodies in infected animals. Through this antibodies one can used as tool for immune diagnostic of this disease. EMA-1 is also a strong candidate to be use as a vaccine in the control of equine theileriosis. In this study we used the Pichia pastoris yeast as expression system for the production of the EMA-1 protein of T. equi and evaluated its antigenicity and immunogenicity. When tested for antigenicity, the recombinant protein was recognized by antibodies form chronic T. equi infected horses, suggesting that epitopes of the native were conserved in the recombinant protein. Also we were able to observe that this protein was immunogenic in mice. The data obtained in this study demonstrated that the yeast P. pastoris is an expression system of heterologous protein suitable for the production of EMA-1 from T. equi.